Pengaruh Metode Demonstrasi Terhadap Pengetahuan tentang Cara Menyikat Gigi Anak Sekolah Luar Biasa (SLB) Bartemeus Malalayang Satu Timur Kecamatan Malalayang Kota Manado - i Ketut Harapan; Youla Karamoy; Putu Gina Sakaranti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2022)
Dental health education should be introduced as early as possible to children so that they can know how to maintain good and correct oral and dental health. Dental health is the most important part in every human life, to achieve optimal dental and oral health, it can be started from increasing knowledge about dental and oral health. Objective: This study aims to determine the effect of the demonstration method on the level of knowledge about how to brush teeth in children at Bartemeus Malalayang Satu Timur special school (SLB). Methods: This type of research was conducted using a one group pretest-posttest design. The research was conducted in June 2022, at the Bartemeus Special School, Malalayang Satu Timur, with a total sample of 25 respondents. The sampling technique used is the total population. The research instrument was a questionnaire to determine knowledge about how to brush teeth and then analyzed using Paired sample t test. The results of the study: The result data showed a significant difference between the pre-test and post-test. Based on the paired sample t-test, it is known that the p value = 0.000 (0.00 0.05), then the research H1 is accepted. Conclusion: Based on the results of the research that has been done, it can be concluded that counseling with the demonstration method of brushing teeth has an effect on increasing knowledge of how to brush teeth.